Screening of germplasm of Abelmoschus against biotic stresses - BADIGER, MAHESH; YADAV, R K (The Indian Journal of Agricultural Sciences, 2019)
Okra [Abelmoschus esculentus (L.) Moench] is an important vegetable of which India is the leading producer, but its yield potential is hampered due to Bhendi Yellow Vein Mosaic Virus (BYVMV) disease and insect pests like whitefly, leafhopper, and shoot and fruit borer. The present study was done to identify the stable sources of resistance. Total 44 accessions of 6 wild Abelmoschus species and 2 check cultivars of A. esculentus (Pusa Sawani and Pusa A-4) were screened under natural field conditions at Division of Vegetable Science, ICAR-IARI, New Delhi during kharif season 2015. Both the check varieties were found susceptible to BYVMV, Jassids, whiteflies, and shoot and fruit borer. Out of 44 accessions of 6 wild Abelmoschus species, 3 accessions, viz. IC306722, IC90476-1 and IC141055 were found highly resistant to BYVMV, only two accessions, viz. IC141055 and IC140986 were resistant to Jassids and only one accession 141055 was resistant to whiteflies. While all the accessions of A. tuberculatus and more than 50% of the accessions of A. manihot var. tetraphyllus and A. moschatus were found resistant to fruit borer. However, one of the wild accession IC141055 showed multiple resistance, i.e. Jassids, whiteflies and fruit borer along with resistance to BYVMV disease indicated its possible importance as source of multiple biotic stress resistance. The mentioned promising accessions can be further screened at different hotspots for confirmation and can be exploited in future breeding programmes for okra improvement.